RETRACTED: Transformation of the vocational training of primary school teachers in the context of bioengineering development - Belovitskaya Svetlana; Shatokhina Irina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001